Effects of Macromolecular Crowding on Folding of Small Globular Proteins - Nguyen, Nhung T. T.; Bui, Phuong Thuy; Hoang, Trinh Xuan (Communications in Physics, 2022)
The effects of inert spherical crowders on the melting temperature and the folding stability of small globular proteins are investigated by using molecular dynamics simulations with a Gō-like model for the proteins. The energy parameter in the Gō-like model is obtained individually for each protein by matching the model’s melting temperature to the experimental meltingtemperature in the absence of crowders. It is shown that both the melting temperature and the folding stability of protein increase in the presence of the crowders. Specifically, as the crowders’ volume fraction φc increases from 0 to 0.4 the melting temperature increases by more than 20 Kelvins, whereas the folding stability is enhanced by up to ∼3.6 kcal/mol depending on the protein and the temperature. At room temperature (300 K), the stability enhancement is 1.2–1.4 kcal/mol, which is close to prior experimental data. It is also shown that the dependence of the folding free energy change on φc can be fitted well to the scaled particle theory by assuming a linear dependence of the effective size of the unfolded state on φc .